Clima laboral y Síndrome de Burnout en el personal del Centro de salud Tipo B Patután. Latacunga. Enero –Abril 2015.Diseño de una Propuesta de Intervención. - Villarroel Vargas, Jenny Fernanda (2016)
The study of the working environment is vitally important because through timely diagnosis could intercede in and thus minimize and control occupational hazards in this case is the burnout syndrome therefore guarantees workers suitable occupational health thus providing quality services and warmth to external users. Objective: To determine the relationship between the working environment and Burnout Syndrome in the Type B Public Health Center of Patután. Method: It is an observational, descriptive – trasversal and correlational research. In which population was 51 workers belonging to Type B Public Health Center of Patután who were administered the questionnaire Workclimate which analized four dimensional such as nature of the work , workgroup, moral stimulation and material conditions of the workplace and the Maslach Burnout Inventory-General Survey (MBI-GS) which assesses emotional exhaustion, cynicism and professional efficacy moda and indexes frequencies used to represent data as well as the Coefficient of Spearman for the relationship between the variables mentioned. Results: The incidence was obtained in terms of the burnout syndrome with a low average level of emotional exhaustion 23.5% in terms of the parameters of the working group and the burnout syndrome found as relationship meaningful with the entire tacts mentioned.